Comprehensive pan-cancer analysis and experiments revealed R3HDM1 as a novel predictive biomarker for prognosis and immune therapy response - Liu, Jiawei; Bing, Zhitong; Wang, Junling (Frontiers in Genetics, 2024)
R3HDM1, a member of the protein family similar to the potential key cancer gene ARPP21 (R3HDM3), has received limited attention in cancer-related research. Leveraging various bioinformatics tools, we uncovered distinct expressions of R3HDM1 across different cancers, indicating its potential as an early diagnostic biomarker, validated within cell lines. Additionally, cell phenotypic experiments were conducted to preliminarily confirm the pivotal role of R3HDM1 in proliferation and migration processes in lung adenocarcinoma cell lines. Furthermore, our study revealed associations of R3HDM1 expression with clinical characteristics of cancer, metabolic pathways, and immune-related pathways. Exploring the relationship between R3HDM1 expression in pan-cancer and infiltration of immune cell subtypes provides valuable insights into the role of R3HDM1 in the tumor immune microenvironment. Overall, this research aims to establish R3HDM1 as a promising molecular marker for predicting cancer patient outcomes and assessing the effectiveness of immune therapy interventions, thereby aiding in the development of more efficient cancer treatments and potential novel anti-tumor therapies, particularly for lung adenocarcinoma patients.